Grinding using cold air cooling - Boswell, Brian; Islam, M.; Ginting, Y.; Ong, J. (2016)
The optimum grinding parameters have always been important in producing the best surface finished workpiece. A parameter deemed essential for obtaining an excellent surface finish is the use of liquid coolant. Unfortunately, large quantities of liquid waste are produced by its use, and it is now imperative that companies implement appropriate waste disposal measures. To date, there have only been a limited numbers of investigations of other methods which do not rely on liquid coolant. Alternative strategies which do not rely on liquid coolant will still require that the ground workpiece is produced to similar surface finish. The goal of this research is to reduce the reliance on liquid coolant, while still producing a suitable standard workpiece.